THE EXPERIENCE OF NURSE ANESTHETISTS IN EDUCATING PATIENTS AND FAMILIES: A QUALITATIVE STUDY - I Wayan Agus Maharyawan; I Ketut Swarjana; I Made Rismawan; Gst. Kade Adi Widyas Pranata (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Effective communication is one of the competencies of nurse anesthetists; they must also play the role of educator to the patients, meaning that they have to disseminate knowledge related to anesthesia to the patients that will undergo the anesthesia process. The communication done by nurse anesthetists may help reduce patients’ anxiety and prepare patients for the post-anesthesia process. Objectives: This study explores the experience of nurse anesthetists in educating patients and families. Methods: This study employed a phenomenological qualitative approach involving 12 nurse anesthetists in Bali. The inclusion criteria for respondents were nurse anesthetists working in the operating room and nurse anesthetists having STRPA and SIPPA. This study took place for 3 months in 2 hospitals. Data were collected through semi-structured interviews with 8 questions. Data collected using in-depth interviews were analyzed using the Colaizzi method. Results: The themes that emerged from this study were “workload of nurse anesthetists”, “uncertainty in documentation results”, and “obstacles in educating patients on anesthesia” that included challenges from patients’ family members, patients, patient management systems, and nurse anesthetists. Conclusion: Limited nurse anesthetists have caused an increased workload, so education related to anesthesia becomes insufficient. v